Outcomes in patients with spinal muscular atrophy given nusinersen, onasemnogene abeparvovec or no treatment: an analysis based on restricted mean survival time. (2nd August 2020) - Bartoli, Laura; Messori, Andrea
ABSTRACT: Objectives: Spinal muscular atrophy (SMA) is a rare neuromuscular disorder. Currently there are two approved drug treatments for SMA: nusinersen and onasemnogene abeparvovec (OAX). The purpose of the present study was to analyze and compare the event-free survival observed in patients with infantile-onset of SMA receiving nusinersen, OAX or no treatment. The comparison was based on the restricted mean survival time (RMST). Methods: The cohorts included in the analyses (nusinersen, 17 patients; OAX, 10 patients; no treatment, 23 patients) were obtained from a standard PubMed search. For each cohort, the values of RMST were determined from the Kaplan-Meier curves reported in these studies (end-point: death or need for permanent ventilation). The RMST was calculated using a model-independent method. Results: The RMST of nusinersen at 33 months of follow up was 25.05 months (95%confidence interval [CI], 23.86 to 26.23) vs 13.90 (95%CI 12.73 to 15.06) for no treatment. The RMST of OAX at 57 months was 57.00 vs 18.32 (95%CI 16.89 to 19.76) for no treatment. Conclusion: Our analyses defined a robust methodological framework to quantify the outcomes of these treatments. This study needs to be repeated after these treatments have achieved a longer follow-up than that presently available.